UNIT 7.44 Flow Cytometry of Murine Spermatocytes. Issue 1 (1st April 2015) - Gaysinskaya, Valeriya; Bortvin, Alex
Abstract : Protocols for purification of murine male germ cells by FACS based on Hoechst 33342 (Ho342) dye staining have been reported and optimized. However, the protocols are often challenging to follow, partly due to difficulties related to sample preparation, instrument parameters, data display, and selection strategies. In addition, troubleshooting of flow cytometry experiments usually requires some fluency in technical principles and instrument specifications and settings. This unit describes setup and procedures for analysis and sorting of male meiotic prophase I (MPI) cells and other germ cells. Included are procedures that guide data acquisition, display, gating, and back‐gating critical for optimal data visualization and cell sorting. Additionally, a flow cytometry analysis of spermatogenesis‐defective testis is provided to illustrate the applicability of the technique to the characterization and purification of cells from mutant testis. © 2015 by John Wiley & Sons, Inc.